2005
DOI: 10.1139/f05-175
|View full text |Cite
|
Sign up to set email alerts
|

Parasitism, space constraints, and gonad asymmetry in the pollan (Coregonus autumnalis)

Abstract: Both sexes of Lough Neagh pollan (Coregonus autumnalis) show directional asymmetry in gonad mass, the left being larger than the right in 70% of individuals. The frequency and degree of asymmetry are size independent in males but become progressively more marked in females of > 120 g somatic mass. There is little evidence to support the hypothesis that the size of the body cavity constrains gonad size. Pollan are heavily and size-dependently infected by metacercariae of the trematode Ichthyocotylurus erraticus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Probably due to their inconspicuous nature, constrictions and asymmetries have not been subject of descriptions in scientific literature until recently. For example, Harrod & Griffiths (2005) observed asymmetrical gonads in pollan Coregonus autumnalis (Pallas) from Loch Neagh, Ireland, in 70% of the population. Also, comparable data have been reported for Lake Constance, where 14% in a sample of 1442 C. lavaretus had gonad strands being >40% different in their mass (Roesch, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Probably due to their inconspicuous nature, constrictions and asymmetries have not been subject of descriptions in scientific literature until recently. For example, Harrod & Griffiths (2005) observed asymmetrical gonads in pollan Coregonus autumnalis (Pallas) from Loch Neagh, Ireland, in 70% of the population. Also, comparable data have been reported for Lake Constance, where 14% in a sample of 1442 C. lavaretus had gonad strands being >40% different in their mass (Roesch, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In male pollan somatic condition, relative liver size and gonad size (Harrod and Griffiths, 2005) all decline with increasing infection intensity. The hepatosomatic index i.e.…”
Section: Costs Of Parasitism In Pollanmentioning
confidence: 96%
“…This parasite has been noted in the lough by earlier workers but there has been no previous assessment of its intensity or impact on pollan. However, Harrod and Griffiths (2005) have shown that I. erraticus affects gonad size and symmetry in pollan.…”
Section: Introductionmentioning
confidence: 98%
“…Given the fact that fish sexual differentiation and gonad development are subject to genetic and environmental influences [7,17], alterations in gonad morphology can be induced both by endogenous and exogenous factors as well as their interaction. Accordingly, gonad abnormalities of fish have been associated, among others, with genetic quality and hybridization status of the broodstock [18,19], autoimmune disease [20], changes in physical water parameters [21,22] or parasite infection [23,24]. One environmental factor that has attracted particular attention as a cause of gonad abnormalities in fish is aquatic contamination by anthropogenic chemicals [4,15,[25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Whitefish species can show considerable morphological variability, which may be related to the genetic divergence and adaptive radiation of coregonids in many lakes of the Northern hemisphere [33][34][35][36][37]. On the other hand, environmental factors such as parasites or anthropogenic contaminants are also known to cause phenotypic variations of whitefish gonads [24,38].…”
Section: Introductionmentioning
confidence: 99%